The Compliance of Ready-Made Spectacle-Wear and Custom-Spectacle-Wear in Refractive Errors Screening - Puti Tiara; Aldiana Halim; Emmy Sugiarti (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
Background: Uncorrected refractive errors that could seriously affect children’s future. The compliance of spectacle-wear has been a problem in refractive errors management in developing countries in terms of the cost, availability and service range of both medical professionals and optical service. Aim: To study the compliance inferiority of ready-made spectacle-wear compared to custom spectacle-wear in refractive errors screening program.Method: Non-inferiority trial research, cluster-randomized trial was conducted to children aged 11-15 years old. Participants with corrected refractive errors (presenting visual acuity <6/12, spherical equivalent -6.00 until +6.00 Diopter (D), astigmatism ?1.00 D, anisometropic ?1.00 D) without other ocular abnormalities were given ready-made spectacles (RMS) and custom spectacles (CS). The observation was carried out in the first (1st) and third (3rd) month; subsequently, non-inferiority test was conducted with 20% margin. Result: Of 1009 school children, 365 were detected with uncorrected refractive errors. Among this number, 220 participants that met the inclusion criteria were prescribed RMS (n = 110) and CS (n = 110). The most common type of refractive errors found was myopia with mild degree of refractive errors. Compliance rate on the first (1st) month for RMS-wear was 63.6% and for CS-wear was 75.5% with d = -11.9% (95% CI -17.95% until -5.85%). Compliance rate on the third month (3rd) for RMS- wear was 65.5% and for CS-wear was 72.7% with d = -7.2% (CI 95% -12.03% until -2.37%). Conclusion: Based on the compliance observation performed in the first (1st) and third (3rd) month, there was no inferiority found among RMS-wear compared to CS-wear. This result could be used as the foundation of RMS use as an alternative for refractive errors management in refractive errors screening program to solve problems in the area of cost, availability and service range of both medical and optical service.